A dental approach to carrier screening in X linked hypohidrotic ectodermal dysplasia. Issue 6 (December 1981) - Spfaer, J A
Abstract : The frequency of carriers of X linked hypohidrotic ectodermal dysplasia among females with hypodontia of the permanent dentition (excluding third molars) could be as high as 1 in 500, and among females with deciduous hypodontia could be as high as 1 in 50. Since it may be possible to identify carriers form among female hypodontia cases in general by virtue of a reduced sweat pore count, the potential exists for a reasonably practical method of screening for carriers at the population level.